MILITARY ETHICS: RETHINKING CIVIL-MILITARY RELATIONS IN BRAZIL - Darlei Dall’Agnol; Gustavo Fornari Dall’Agnol (Kriterion, 2023)
ABSTRACT This paper presents a solid normative approach in military ethics, which justifies the rule of law in a constitutional regime capable of fixing the proper role of the Armed Forces in Brazil. Deploying this ethical framework, it analyzes the relevant literature, especially authors who defend civilian supremacy for the good functioning of a democratic society. Afterwards, some models of civil-military relations are introduced to establish the parameters and indicators of proper democratic consolidation. These parameters are applied to recent events, revealing that Brazil is regressing in its civilian control over the military. Finally, some practical proposals for reversing this tendency are put forward in pursuit of a fully democratic regime in Brazil.